Social inclusion and higher education - Basit, Tehmina N.; Tomlinson, Sally (Policy Press, 2012)
This text examines the experiences of students in higher education from 'non-traditional' backgrounds. It demonstrates that the students and their families are finding ways of acquiring forms of capital that encourage and sustain their participation.